Microorganisms from harsh and extreme environments: a collection of living strains at ACUF (Naples, Italy) - D’Elia, Luigi; Del Mondo, Angelo; Santoro, Mariano; De Natale, Antonino; Pinto, Gabriele; Pollio, Antonino (Ecological Questions, 2018)
The Algal Collection at the University Federico II (ACUF) is a bioresource center where over 800 live microalgal strains are maintained, mainly belonging to Cyanobacteria, Chlorophyta, Rhodophyta, and Bacillariophyceae. The extremophilic algae maintained at ACUF include thermo-acidophilic and acidotolerant strains, mostly belonging to the Cyanidiophyceae isolated from European and extra-European sites, and also terrestrial isolates from bare rocks and monuments. The main target of the ACUF Center is the study and preservation of the diversity of extremophylic microalgae. This collection is used as a resource for studies about biochemical and evolutionary strategies as well as mechanisms involved in cell functioning under harsh environmental conditions. These organisms can be also useful sources for the production of chemical compounds or other biological products with potential biotechnological applications.